Legal Politics and State Responsibility in Addressing Adolescent Stunting: Fulfilling the Right to Health in West Java - Asep Abdul Sahid; Ambar Sulianti; Adam Faruqi; M. Ridha Taufiq Rahman (Khazanah Hukum, 2026)
This article examines adolescent stunting as a legal and human rights issue within the framework of the right to health in Indonesia. It argues that the problem should be assessed not only through health intervention outcomes, but also through the legal politics of policy implementation and state responsibility under Presidential Regulation No. 72 of 2021 on the Acceleration of Stunting Reduction. Using an empirical legal approach with a socio-legal orientation, the study analyzes the implementation of the anti-stunting policy in Garut Regency, Majalengka Regency, and West Bandung Regency, drawing on legal materials, interviews, observations, questionnaires, and supporting empirical data. The findings show that adolescents are materially affected by stunting and respond positively to structured measures, yet they remain weakly prioritized in operational anti-stunting governance, which continues to focus more explicitly on pregnant women and children under five. Local institutions have undertaken meaningful action, but implementation remains fragmented and dependent on local initiative rather than on a clearly standardized rights-based framework. This article concludes that adolescent stunting reflects a gap between normative guarantees and policy implementation, and that stronger legal recognition, local accountability, and adolescent inclusion are necessary for the fuller realization of the right to health.